2019
DOI: 10.3390/ijms20246233
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Extracellular Vesicles in Children with OSA Disrupt Blood–Brain Barrier Integrity and Endothelial Cell Wound Healing In Vitro

Abstract: Pediatric obstructive sleep apnea (P-OSA) is associated with neurocognitive deficits and endothelial dysfunction, suggesting the possibility that disruption of the blood–brain barrier (BBB) may underlie these morbidities. Extracellular vesicles (EVs), which include exosomes, are small particles involved in cell–cell communications via different mechanisms and could play a role in OSA-associated end-organ injury. To examine the roles of EVs in BBB dysfunction, we recruited three groups of children: (a) absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 76 publications
(95 reference statements)
0
23
0
Order By: Relevance
“…The cellular changes cause the formation and release of EVs, which could pass through the BBB and be detectable in the blood. The stimuli could be stress hormones, cytokines as part of inflammatory processes, and/or EVs from peripheral blood 32 . A study of children with obstructive sleep apnea found that EVs in peripheral blood disrupted the integrity of the BBB, especially in those with neurocognitive deficits 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cellular changes cause the formation and release of EVs, which could pass through the BBB and be detectable in the blood. The stimuli could be stress hormones, cytokines as part of inflammatory processes, and/or EVs from peripheral blood 32 . A study of children with obstructive sleep apnea found that EVs in peripheral blood disrupted the integrity of the BBB, especially in those with neurocognitive deficits 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The stimuli could be stress hormones, cytokines as part of inflammatory processes, and/or EVs from peripheral blood 32 . A study of children with obstructive sleep apnea found that EVs in peripheral blood disrupted the integrity of the BBB, especially in those with neurocognitive deficits 32 . Further studies are needed to better understand the processes that allow release of astrocyte-derived EVs from the CNS into peripheral blood after exposure to stress and the clinical relevance of this.…”
Section: Discussionmentioning
confidence: 99%
“…However, such pro-inflammatory interleukin activation is not constant in OSAS patients and more particularly in adults and in the elderly. Furthermore, microparticles described in OSAS sera patients could lead by themselves to endothelial dysfunction at the brain vascular scale and could alter BBB permeability, like as found in an exosome 46,47 . Indeed, serum factors are not yet identified, and inflammation remains a hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Morning first void mid-stream urine samples will be collected after each of the two PSG in two 50 mL aliquots that will be immediately stored at −70 degrees until their analysis in the laboratory of the Department of Child Health at the University of Missouri School of Medicine at Columbia, MO, USA. After appropriate aliquoting and initial centrifugation and vortexing, isolation of exosomes will be performed as previously reported [ 66 , 67 ]. Circulating miRNAs are in body fluids such as in urine and are packaged in secreted urinary extracellular vesicles which protect them from degradation.…”
Section: Methodsmentioning
confidence: 99%